The Contribution to the Research on Territorial Structure and Borders Of Pergrini’s Communities Deremistas and Doclea - Samardžić, Gligor; Mlađenović, Marijana (Collection of Papers of the Faculty of Philosophy in Priština, 2020)
The paper presents data on peregrini’s communities (civitates peregrinae) Deremistas and Doclea in the south of Illyricum. Their citizens had the status of the locals and mostly the status of peregrinus, i.e. non-Roman. One of the priorities of the implemented Roman rule on this territory was the organization of the local citizens. It meant the formation of communities, setting borders among territories and splitting taxes. These civitates stopped being independent tribes since the implementation of the Roman rule and were turned into Roman administrative units. The Roman government categorized the locals according to administrative and legal regulations, which represented the first step in their integration. The epigraph statues (Kosijerevo, Riječani) represent precious testimonies on setting borders among the territories, the status, and, frequently, integral inner structure of the community. The epigraph materials show that the research on territorial structure of peregrini’s communities divides civitates, according to their inner territorial structure, into smaller units: pagi, vici, castella. Castellа can be found as the terriorial unit near Deremistas and Doclea (Riječani, Plana). The epigraph statues and oral sources shed light to a certain extent on these findings in the south of the province of Dalmatia.